DETERMINANT ANALYSIS OF LABOR ABSORPTION IN NORTH SUMATRA - Reni Ria Armayani; Anriza Witi Nasution; Nurmala; Sugianto; Iskandar Muda (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
As for the ways and efforts to increase the number of workers at work, there may be several influencing factors including: UMP, GRDP, Investment, Inflation and Exports. The research was conducted to examine the number of workers absorbed in North Sumatra for the 2011-2020 period so that it can be studied. This type of data uses secondary data from BPS, Sakernas (National Labor Force Survey), and the Ministry of Manpower. The method was studied using a quantitative associative approach with multiple linear regression models assisted by the E-views 9.0 computer program. The results of data processing stated that the UMP, Investment and Export had a positive effect. GRDP and Inflation have a negative effect. positive and negative signs on each variable explain that a positive sign if there is an increase in each independent variable has an impact on the increase in the dependent variable and vice versa. Variables that are not significant are UMP, Investment, and Inflation. Meanwhile, the significant variables are GRDP and Exports.